Patients with STEMI after Revascularization: Is There a Relationship Between Coronary Artery Lesion and Renal Function? - Anna V. Broniuk; Lesia V. Rasputina (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To establish the relationship between coronary bed lesions and glomerular filtration rate (GFR) calculated on the basis of creatinine, cystatin C and urine albumin-creatinine ratio in patients with ST-elevation myocardial infarction (STEMI) who underwent percutaneous coronary intervention.Materials and methods. We examined 286 patients with STEMI, aged 39 to 87 years (mean age 62.8 ± 9.8, median age 64, interquartile range 56 to 71 years), 202 (70.6%) were men and 84 (29.4%) were women. All the patients underwent general clinical tests, coronary angiography with subsequent percutaneous coronary intervention, and echocardiography.Results. The most frequent infarct-related coronary artery (CA) was the anterior interventricular branch of the left coronary artery in the proximal and middle segments, and the right coronary artery in the proximal segment. In general, there was no significant difference in the number of affected CAs among the examined patients. The division of patients into groups according to the level of GFR, determined both on the basis of creatinine and cystatin C, did not reveal significant differences in the distribution of infarct-related CAs. At the same time, the number of patients with multivessel lesions significantly increases with decreased GFR. Depending on the level of the urinary albumin-to-creatinine ratio, a significant increase in the number of patients with two- and multivessel lesions of the CAs was noted.Conclusions. Close correlations between multivessel lesions of CAs and gender, age, urinary albumin-to-creatinine ratio, GFR, left and right atrial size, duration of history of hypertension and diabetes mellitus, presence of II-III degree atrioventricular block and mortality were established.